Roles of myokines in osteoporosis under physiological and diabetic conditions - Ji, Xing; Hu, Xinhua; Xu, Taotao; Yang, Wanlei (Frontiers in Endocrinology, 2025)
The musculoskeletal system is not only closely linked anatomically, but muscle-derived myokines also play a crucial role in bone development and metabolism beyond the effects of mechanical force. Myokines are essential in muscle-bone crosstalk, significantly influencing bone remodeling and metabolism. In the context of diabetes, including both type 1 (T1DM) and type 2 (T2DM), changes in myokine expression have a substantial impact on bone metabolism, leading to an increased risk of osteoporosis. This review provides a comprehensive examination of the roles of key myokines in regulating osteoblast lineage cells and osteoclast activity. We highlight how different myokines can either promote or inhibit bone formation and resorption and discuss their altered expression levels under diabetic conditions. A deeper understanding of the multifaceted roles of myokines may open new avenues for treating osteoporosis, particularly in diabetic patients.